P Pelatihan Instalasi Dan Pengenalan Crystal Reports Dalam Visual Basic.Net Pada PT.Ratimdo Utama - Ramadhan, Hari (LPPM Universitas Potensi Utama, 2023)
PT.Ratimdo Utama is a company engaged in the production of wood. For systems in production movement, recording is carried out using a computerized system where the system is built with the Visual Basic.Net application. However, running applications require reports to see the production movement. A runtime application is needed on each client computer so that system reports can display wood production data and staff or employees at PT. Ratimdo Utama require training, therefore a Crystal Report is needed to support the reports that will be displayed later. This activity can provide knowledge about the uses of several components contained in the Crystal Report application and can provide insight and knowledge about how to install the Crystal Report application for Visual Basic.Net for staff or employees at PT.Ratimdo Utama.